2022
DOI: 10.1002/tox.23701
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to copper activates mitophagy and endoplasmic reticulum stress‐mediated apoptosis in chicken (Gallus gallus) cerebrum

Abstract: A large amount of copper (Cu) used in production activities can lead to the enrichment of Cu in the environment, which can cause toxicity to animals. However, the toxicity mechanism of Cu on the cerebrum is still uncertain. Hence, a total of 240 chickens were separated into four groups in this study to reveal the potential connection between mitophagy and endoplasmic reticulum (ER) stress-mediated apoptosis in the chicken cerebrum in the case of excess Cu exposure. The cu exposure situation was simulated by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…4 ). First, although copper is essential for autophagy, high concentrations of copper might induce mitophagy by generating mtROS [ 151 153 ], altering mitochondrial membrane potential or inhibiting mTOR activity [ 154 , 155 ]. Cells reduce the copper content through this negative feedback way of copper-induced mitophagy to maintain homeostasis, but studies have shown that copper has an inhibitory effect on autophagy.…”
Section: Mitochondria and Other Metalsmentioning
confidence: 99%
“…4 ). First, although copper is essential for autophagy, high concentrations of copper might induce mitophagy by generating mtROS [ 151 153 ], altering mitochondrial membrane potential or inhibiting mTOR activity [ 154 , 155 ]. Cells reduce the copper content through this negative feedback way of copper-induced mitophagy to maintain homeostasis, but studies have shown that copper has an inhibitory effect on autophagy.…”
Section: Mitochondria and Other Metalsmentioning
confidence: 99%